Fakhr Al-Din Al-Razi: a systematic review on literature found in Indonesia - Nur Farhana Baharuddin; Saadah Abd Rahman; Hishomudin Ahmad; Hazleena Baharun (IAEME Publication, 2024)
Al-Razi, a philosopher, theologian, and exegetist in the history Islamic thought, was one prominent Muslim scholar that had contributed in interpreting the al-Quran. Numerous studies have been conducted on this remarkable scholar and his outstanding works in Middle East and European countries, however, Indonesian studies have not been extensively highlighted. Thus, the present study aims to analyze studies conducted by Muslim Indonesian scholars on al-Razis works published in Indonesia between 2008 and 2016. The researcher employed Systematic Literature Review (SLR) as its main methodological tool with the adaptation of PRISMA technique. Findings revealed that Muslim Indonesian scholars mainly focused on three core subjects when they studied the works of al-Razi. The first was specific themes found in the Quran namely Oneness of Allah and His creation, the societal relationship in community, and Islamic philosophy on human creation. Second, comparative studies between al-Razi and other prominent Muslim scholars. Finally, the methodology used by al-Razi when interpreting the Quran. This study shows that Al-Razis works are so diverse and relevant that they are often referred to by present Indonesian Muslim scholars. Thus, it can be concluded that al-Razis works are very much pertinent and significant even in the modern world. IAEME Publication.